Revision of Acrulia Thomson, 1858 and Dialycera Ganglbauer, 1895, with taxonomic notes on related genera and description of a new genus from the Caucasus (Coleoptera: Staphylinidae: Omaliinae: Omaliini) - Shavrin, Alexey V.; Zanetti, Adriano (Zootaxa, 2020)
Two Palaearctic genera of the tribe Omaliini McLeay, 1825 are revised, redefined, and discussed: Acrulia Thomson, 1858, containing A. inflata (Gyllenhal, 1813), A. assingi Zanetti & Shavrin, sp.n. (Greece: Thessalia, Pelopónnisos), and A. akbesiana (Pic, 1898), revalidated from the synonymy with Dialycera aspera (Eppelsheim, 1889), and the genus Dialycera Ganglbauer, 1895, containing D. distincticornis (Baudi di Selve, 1870), D. aspera and D. minuta Luze, 1906. Taxonomic and faunistic notes for three species of the genus Acruliopsis Zerche, 2003 (A. denticollis (Sharp, 1889), A. tumidula (Mäklin, 1853) and A. ussuriensis Zerche, 2003) and four Palaearctic species of the genus Hapalaraea Thomson, 1858 (H. alutacea (Reitter, 1909), H. armeniaca (Székessy, 1939) comb.n. (from Acrulia), H. pygmaea (Paykull, 1800), and H. settei Zanetti, 1983) are provided. Hapalaraea alutacea and H. armeniaca are redescribed. Pseudodialycera Zanetti & Shavrin, gen.n., with the type species P. striatripennis (Aubé, 1850) comb.n. (from Dialycera) from the Caucasus, is described. A neotype for Acrulia akbesiana, and lectotypes for Omalium asperum Eppelsheim, 1889, O. inflatum Gyllenhal, 1813, and Phyllodrepa (Hapalaraea) alutacea Reitter, 1909 are designated. The following two synonymies are established: Acrulia akbesiana = Dialycera bimaculata Luze, 1906 syn.n., Hapalaraea pygmaea = Acrulia angusticollis Reitter, 1909 syn.n. The main morphological structures, including the genitalia and terminalia, are figured. Zoogeographic data are provided and mapped (except for Hapalaraea). Keys to the species of Acrulia and Dialycera, and a key to studied genera of Omaliini are provided. Several new records are reported: Acrulia inflata from Estonia, Greece, and Kazakhstan, Dialycera distincticornis from Montenegro and Greece, D. aspera from Greece and Jordan, and D. minuta from Armenia, Turkey, Lebanon and Jordan.